2021
DOI: 10.1088/1742-6596/1727/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of density thresholding on the EEG network construction

Abstract: The procedure of thresholding for graph construction is one of the common steps in calculating networks of brain connections. However, this procedure can lead to incomparable results from different studies. In the present study we aim to test the effect of thresholding or algorithmic reduction of the number of connected nodes on the construction of a set of widely used connectivity graph metrics derived from EEG data. 164 people took part in our study. Participants were recruited via social networks. EEG was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The article is based on a study first reported in the Journal of Physics: Conference Series 22 and presents an extended analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The article is based on a study first reported in the Journal of Physics: Conference Series 22 and presents an extended analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The article is based on a study first reported in the Journal of Physics: Conference Series (Zakharov et al, 2021) and presents the extended analysis.…”
Section: Introductionmentioning
confidence: 99%